The Synergistic Role of Sulfuric Acid, Bases, and Oxidized Organics Governing New‐Particle Formation in Beijing. Issue 7 (8th April 2021) - Yan, Chao; Yin, Rujing; Lu, Yiqun; Dada, Lubna; Yang, Dongsen; Fu, Yueyun; Kontkanen, Jenni; Deng, Chenjuan; Garmash, Olga; Ruan, Jiaxin; Baalbaki, Rima; Schervish, Meredith; et al.
Abstract: Intense and frequent new particle formation (NPF) events have been observed in polluted urban environments, yet the dominant mechanisms are still under debate. To understand the key species and governing processes of NPF in polluted urban environments, we conducted comprehensive measurements in downtown Beijing during January–March, 2018. We performed detailed analyses on sulfuric acid cluster composition and budget, as well as the chemical and physical properties of oxidized organic molecules (OOMs). Our results demonstrate that the fast clustering of sulfuric acid (H2 SO4 ) and base molecules triggered the NPF events, and OOMs further helped grow the newly formed particles toward climate‐ and health‐relevant sizes. This synergistic role of H2 SO4, base species, and OOMs in NPF is likely representative of polluted urban environments where abundant H2 SO4 and base species usually co‐exist, and OOMs are with moderately low volatility when produced under high NOx concentrations. Plain Language Summary: Atmospheric new particle formation (NPF) is a dominant source of atmospheric ultrafine particles worldwide. Those particles profoundly influence climate and human health. NPF includes two consecutive processes, that is, the formation of new particles (∼2 nm in diameter) and their subsequent growth to larger sizes. Extensive studies conducted in the laboratory and in forested areas have shown that many gaseous species can participate in NPF, such as sulfuric acid, ammonia, amines, and oxidize organic molecules. However, the actual roles of these vapors may vary significantly from location to location and are largely unclear in urban environments. Here, based on measurements of sulfuric acid, sulfuric acid clusters, and oxidize organic molecules, we demonstrate that sulfuric acid and base molecules were responsible for the initial formation of new particles during a wintertime field campaign in Beijing. The majority of oxidized organic molecules had a minor contribution to the formation of new particles but were crucial for particle growth above 2–3 nm to climate‐ and health‐relevant sizes. Key Points: Process‐level understanding of new particle formation (NPF) in wintertime Beijing was obtained based on measurement state‐of‐the‐art instruments The analysis of sulfuric acid cluster composition and budget showed that sulfuric acid‐base clustering initiated NPF Condensable organic vapors were characterized and demonstrated to have a crucial influence on the growth of newly formed particles